2007
DOI: 10.1007/s10342-006-0140-8
|View full text |Cite
|
Sign up to set email alerts
|

Effects of enhanced hydraulic supply for foliage on stomatal responses in little-leaf linden (Tilia cordata Mill.)

Abstract: Responses of leaf conductance (g L ) to variation in environmental and plant hydraulic factors were examined on intact and detached shoots of little-leaf linden (Tilia cordata Mill.) with respect to branch position in the crown. Using detached shoots, we manipulated leaf water supply and light availability in order to separate the effects of insufficient hydraulic supply and low irradiance. The intact upper-crown leaves demonstrated 2.0-2.2 times higher (P < 0.001) daily maxima of g L compared to the lower-cro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 61 publications
1
11
0
Order By: Relevance
“…They found mean maximum g L between 100 and 300 mmol m −2 s −1 in a four-year period with the lowest values reported during the dry year 2003. For T. cordata, our diurnal mean maximum g L values agree with the measurements reported by Niinemets et al (1999), and Sellin and Kupper (2007).…”
Section: Species Differences In Leaf Conductance and Leaf Water Potensupporting
confidence: 90%
“…They found mean maximum g L between 100 and 300 mmol m −2 s −1 in a four-year period with the lowest values reported during the dry year 2003. For T. cordata, our diurnal mean maximum g L values agree with the measurements reported by Niinemets et al (1999), and Sellin and Kupper (2007).…”
Section: Species Differences In Leaf Conductance and Leaf Water Potensupporting
confidence: 90%
“…Leaves account for a majority (50-90%) of the hydraulic resistance to water flow through shoots of trees (Yang and Tyree 1994;Nardini and Salleo 2000;Nardini 2001), and thus form a substantial part of the whole resistance of the water transport pathway from soil to leaves (Sack et al 2003;Sack and Holbrook 2006;Sellin and Kupper 2007a). However, not in all cases, majority of the total hydraulic resistance occurs at the leaf level (Gyenge et al 2005).…”
Section: Vertical Patterns Within a Crownmentioning
confidence: 98%
“…Opposite patterns of hydraulic capacity have often been revealed within crowns of both coniferous and broad-leaved trees: specific hydraulic conductivity of branches (Protz et al 2000;Lemoine et al 2002;Jerez et al 2004;Burgess et al 2006) or shoot hydraulic conductance increased with branch height in the crown (Aasamaa et al 2004). Also apparent soil-to-leaf hydraulic conductance (G T ), defined as a current transpiration rate divided by water potential drop from soil to leaves (Meinzer et al 1995;Wullschleger et al 1998), has been shown to increase from basal to top branches (Sellin and Kupper 2004, 2005a, 2007a. Thus, qualitatively different phenomena can be observed within a crown.…”
Section: Introductionmentioning
confidence: 96%
“…Species with greater K As displayed greater leaf gas exchange values consistent with previously reported correlations (Bond and Kavanagh 1999;Sperry et al 2002;Hernández et al 2009). High photosynthetic rates and the correspondingly high stomatal conductance must be supported by high hydraulic conductance (Mencuccini and Comstock 1999;Hubbard et al 2001;Sellin and Kupper 2007). Under optimal soil water supply, high K As allows more efficient water transport from stems into photosynthetic organs to compensate leaf water loss and consequently maintain daily water potential high (Ackerly 2004;Jacobsen et al 2007b).…”
Section: Morphological Traits Among Speciesmentioning
confidence: 99%